2015
DOI: 10.1177/2156587215621461
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Chiropractic Services in Military and Veteran Health Care Facilities

Abstract: This literature review examined studies that described practice, utilization, and policy of chiropractic services within military and veteran health care environments. A systematic search of Medline, CINAHL, and Index to Chiropractic Literature was performed from inception through April 2015. Thirty articles met inclusion criteria. Studies reporting utilization and policy show that chiropractic services are successfully implemented in various military and veteran health care settings and that integration varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 98 publications
(145 reference statements)
0
25
0
Order By: Relevance
“… 20 Previous work indicates that the use of VA chiropractic services has grown substantially since its inception, as currently upward of 46,000 veterans are being served, and that doctors of chiropractic (DCs) working in VA manage LBP through the delivery of evidence-based, nonpharmacological services. 21 24 Although the use of chiropractic care in VA has expanded, 23 few data exist to inform optimal models of access to and delivery of chiropractic care, in VA or elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Previous work indicates that the use of VA chiropractic services has grown substantially since its inception, as currently upward of 46,000 veterans are being served, and that doctors of chiropractic (DCs) working in VA manage LBP through the delivery of evidence-based, nonpharmacological services. 21 24 Although the use of chiropractic care in VA has expanded, 23 few data exist to inform optimal models of access to and delivery of chiropractic care, in VA or elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of chiropractic services in VA presents a novel opportunity to explore strategies to improve collaborative case management for patients with LBP, including those with mental health comorbidity. 24 , 25 One aim of our research project, Collaborative Care for Veterans with Spine Pain and Mental Health Conditions, was to develop a consensus-based, chiropractic integrated care pathway to guide clinical decision making and improve communication and referral processes between DCs, primary care providers, and mental health professionals who manage veterans with LBP in VA healthcare facilities. Care pathways are health care tools designed to support evidence-based practices, clinical decision making, and the organization of care processes for providers treating patients with well-defined health conditions, such as those with LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Most DCs surveyed reported working in interprofessional practice settings in which they either co-managed patient care or collaborated with a diverse group of health care providers, which is similar to recent studies of chiropractic integration in military or VA hospital settings. 4,15 These DCs most often consulted with or referred patients to primary care providers and other health professionals who focus on the management of pain and physical function. Because many were co-located, these DCs participated in such referrals on a daily or weekly basis, engaged in frequent face-to-face discussions with medical physicians and other health care providers, and shared electronic health records.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Over the past 2 decades, large public sector health care delivery systems in the United States, including the Department of Defense and Department of Veterans Affairs (VA), have integrated chiropractic care into their offered services. [3][4][5] Private sector medical settings, ranging from small primary care clinics to large health care systems in the United States, have introduced chiropractic care. [6][7][8][9][10] A survey by the National Board of Chiropractic Examiners Practice Analysis of Chiropractic reported that 9% of doctors of chiropractic (DCs) practice in settings other than chiropractic offices, including 7.8% who work in an "integrated health care facility," with 3.6% of those surveyed identifying that they hold hospital staff privileges.…”
Section: Introductionmentioning
confidence: 99%
“…Our informal search in Pubmed using the search terms “chiropractic OR chiropractor” reveals a 54% increase in publications between 2002 and 2016 (216 versus 401 publications). Hence, we have a better understanding than ever before of the education of chiropractors [ 7 , 8 ], the types of therapies used by chiropractors [ 9 – 11 ], the conditions treated by chiropractors [ 10 – 13 ], the effectiveness [ 14 – 16 ] and cost-effectiveness of chiropractic care [ 17 , 18 ], safety and side effects of chiropractic treatment [ 19 , 20 ], and settings where chiropractors function alone or in collaboration with other healthcare providers [ 21 23 ]. In spite of this, there is still not a clear picture of what comprises the chiropractic profession, and how chiropractors contribute to the health of individual patients and populations.…”
Section: Introductionmentioning
confidence: 99%